استخدام المشتقات المالية في إدارة المخاطر المالية - سهام, عيساوي; لخضر, مرغاد (Recherches économiques et managériales; Vol. 15 (2014): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(JUIN), 2014)
يشير قوة نمو المشتقات المالية إلى أن المشاركين في السوق تجدها أدوات مفيدة لإدارة المخاطر. فيمكن للبنك التجاري استخدامها لإدارة مخاطر محفظة قروضه، كما يمكن للبنك الاستثماري استخدام المشتقات المالية لإدارة المخاطر التي يتكبدها عند الاكتتاب في الأوراق المالية، ويستخدم المستثمرون (مثل شركة التأمين، وصناديق التحوط) المشتقات المالية لتخفيف المخاطر المالية التي يتعرضون لها. ومع ذلك، فالمشتقات المالية تشكل تحديات إدارة المخاطر الخاصة بها، فيجب على المشاركين في السوق فهمها ودراستها لمواجهة مخاطر استخدام هذه الأدوات. الكلمات المفتاحية: إدارة المخاطر المالية، المشتقات المالية Research Summary  : The striking growth of financial derivatives suggests that market participants find them to be useful tools for risk management. A commercial bank can use it to manage the risk of its loan portfolio, An investment bank can use financial derivatives to manage the risks it incurs when underwriting securities, and Investors (such as the insurance company,hedge funds), used financial derivatives to mitigate the financial risks faced by them. However, financial derivatives pose risk management challenges of their own. Participants must understand and study it to face the risks of using these tools. Key words : financial risk management, financial derivatives.